An accessibility learning system for higher integrated education of hearing-impaired students technology. (11th December 2020) - Jian, Zhao; Liu, Wang; Lijuan, Shi; Zhejun, Kuang; Di, Zhao
Integrated education for the disabled is the embodiment of social equity and social progress; China has carried out the pilot work of integrated higher education for deaf students for four years. However, in the actual teaching process, it is found that the learning efficiency and effect for deaf students are quite different from that for healthy students. This difference is mainly caused by hearing impairment. Hearing-impaired students are accustomed to understanding the semantic meaning mainly through lip language. However, the amount of information of lip language of hearing-impaired students decreases due to distance, shielding and other interference reasons, which lead to the semantic understanding obstacle of course teaching. An accessibility learning system for higher integrated education of hearing-impaired students is established to help them capture the auxiliary information of teachers' lip language and voice. It is also evaluated to explore its practical application effect. The evaluation results show that this system can help hearing-impaired students better understand the semantic meaning of the course and integrate into the education classroom.